Self-Efficacy Beliefs in Science Teaching of Class Teachers in Tartous City - Solemon , Reem; Sbeira , Fouad; Ibrahim , Rima (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to explore self-efficacy beliefs in science teaching of class teachers, and to investigate whether these beliefs are different among participants according to general secondary school branch and years of teaching experience. The sample consisted of(70)subjects. Science Teaching Efficacy Belief Instrument was used. The results were: The class teachers had positive self-efficacy beliefs in science teaching on the overall scale. There was significant difference between the mean scores of class teachers on the overall scale according to (general secondary school branch , years of teaching experience) in favor of the teachers who studied the scientific branch, and who had (7and less than 11) years of teaching experience, and there was an effective impact of the two variables interaction on self-efficacy beliefs. The research recommended that carrying further researches about the effects of another variables on Self-Efficacy beliefs in science teaching.